Standarisasi Lintasan Kerja Penjahitan Sepatu pada PT XYZ - Cerianto Chandra; I Gede Agus Widyadana (Jurnal Titra, 2017)
PT. XYZ is a company engaged in manufacturing shoes. Work line at PT. XYZ have two varies cause many differences. The purpose of this study is to standardize the existing work line on PT.XYZ with the same number of people in the work line. The research was done by getting the raw time of shoes, shoe making sequence, production capacity, and working hours. Determination of the number of operators is done by line balancing in the hope that the number of people selected can have the desired line balance variance. Layout arrangements are required to support the selection of proposed work line. The results of the analysis show that the number of operators is 47 people with line balance variance of 92%. The total capacity that can be obtained with 47 people is 69613 pairs, greater than the current total production of 69493. The number of required operators reduced 40 people compared with the current conditions. The required investment cost is Rp. 1,849,070,000